Ways and Measures of Restoring Vegetation for Controlling Soil and Water Loss on the Loess Plateau of China - Qinxiao, Wu; Xiangdong, Liu; Hongyan, Zhao (Indian Forester, 1995)
On the Loess Plateau much more urgent problem is how to reduce soil and water loss via restoring vegetation, and turn the weak ecology to a fine state. This is also a dominant and long-term task faced in whole mid-western China. By comprehensive and perennial researches on this area, the scientists in North-western Institute of Soil and Water Conservation summarize a series of ways and measures to recover the vegetation on the Loess Plateau. The main work is to select those tree and grass species which finally fit the local eco-environment, to quickly close the barren hills and plateaus .via aerosowing tech. and so on. At the same time, we also give considerations to the immediate economic interests and long-term productivity in order to mobilize all positive factors of local masses for conserving and rebuilding the vegetation. This paper is a brief introduction on the works under this certain background which may interest the colleagues in the world.